RHEOLOGICAL PROPERTIES ASSESSMENT OF CARP FEED MIXTURES WITH DIFFERENT PROTEIN SOURCES INCLUDED USING MIXOLAB - Ilić, Petar; Banjac, Vojislav; Hadnađev, Miroslav; Pojić, Milica; Vidosavljević, Strahinja; Stojkov, Viktor; Tiwari, Brijesh (Food and Feed Research, 2025)
Three carp diets with same starch content (approximately 230 g/kg) with the inclusion of different protein sources were formulated. Control feed contained fish meal and soybean meal as a main source of protein which were completely substituted by dried duckweed. All ingredients of the diets were finely ground at the hammer mill and then mixed in twin-shaft paddle mixer. The aim of this paper was to assess the rheological and thermomechanical properties of these mixtures in order to forecast their behavior during subsequent processing. The determination of rheological properties was performed by Mixolab where water absorption capacity was set at a constant value of 100%. The Mixolab curve profiles varied where diet in which the fishmeal was completely replaced by the novel plant protein ingredient, duckweed flour, displayed greatest resistance to deformation, therefore the highest water holding capacity which was in accordance with results obtained by the method used for assessment of water absorption properties. Obtained results demonstrated that Mixolab has a good potential to be used as a tool for screening dry feed mixes when taking into account the amount of water and steam necessary for the successful conditioning management. Further investigation is required to enhance the applicability of these methods in establishing more effective parameters during the conditioning process.